2020
DOI: 10.1172/jci138697
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of paracellular cation-selective claudin-2 channels attenuates immune-mediated experimental colitis in mice

Abstract: the larger cations tetramethylammonium, tetraethylammonium, or N-methyl-D-glucamine (Figure 1E). This size-selective permeability increase is characteristic of claudin-2 channel activity (14-16, 48-50), but does not exclude the possibility that other cation-selective pore-forming claudins, e.g., claudin-15 (10, 13, 22), contribute to IL-13-induced barrier loss in vivo. We therefore asked if claudin-2 was required for IL-13-induced barrier loss. Prior to IL-13 treatment, paracellular permeability was similar in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 77 publications
3
86
0
Order By: Relevance
“…Recent work by Raju et al has shown that increased expression of Claudin-2 enhances immune mediated colitis specifically via the pore pathway and not via the leak pathway; however, they also showed that Cldn2 −/− were protected from the immune mediated increase in the leak pathway 34 . The pleiotropic nature of tight junctional proteins, specifically Claudin-2, suggests that changes in expression may have effects on both the leak and pore pathway 35 .…”
Section: Discussionmentioning
confidence: 97%
“…Recent work by Raju et al has shown that increased expression of Claudin-2 enhances immune mediated colitis specifically via the pore pathway and not via the leak pathway; however, they also showed that Cldn2 −/− were protected from the immune mediated increase in the leak pathway 34 . The pleiotropic nature of tight junctional proteins, specifically Claudin-2, suggests that changes in expression may have effects on both the leak and pore pathway 35 .…”
Section: Discussionmentioning
confidence: 97%
“…Intestinal epithelial claudin‐2 expression can be upregulated in vivo by IL‐13 or IL‐22 as well as enteric infection and immune‐mediated disease (Epple et al., 2017; Heller et al., 2005; Ong et al., 2020; Raju et al., 2020; Schumann et al., 2012; Tsai et al., 2017). In Citrobacter rodentium infection, IL‐22‐induced claudin‐2 upregulation increases paracellular permeability to creatinine (6 Å diameter), but not 4 or 70 kDa dextran (28 and 120 Å diameter), within 2 days of infection.…”
Section: Commentarymentioning
confidence: 99%
“…Studies of knockout mice lacking claudin‐2 and transgenic mice overexpressing intestinal epithelial‐specific claudin‐2 have shown that this claudin‐2‐dependent permeability promotes pathogen clearance and is protective in C. rodentium infection (Tsai et al., 2017). Conversely, claudin‐2 upregulation in immune‐mediated experimental inflammatory bowel disease promotes disease progression by poorly understood mechanisms (Raju et al., 2020).…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations